Immunoregulatory activities of polysaccharides from mung bean. (30th March 2016) - Yao, Yang; Zhu, Yingying; Ren, Guixing
Highlights: Two polysaccharide sub-fractions were isolated and purified after ultrasonic treatment with mung bean polysaccharide. Their structural features were analyzed using FT-IR and HPSEC–MALLS–RID. The ultrasonic treatment polysaccharides showed significantly immunoregulatory activities. Abstract: Ultrasonic treatment was performed on water-extractable polysaccharides from the seed of mung beans. Purified by anion-exchange and gel filtration chromatography, MWP-1′ and MWP-2′ were obtained. Average molecular weights ( M w s) of MWP-1′ and MWP-2′ were 68.4 kDa, and 52.4 kDa, respectively. Monosaccharides components analysis indicated that MWP-1′ was composed of Rha, Ara, Man and Gal in a molar percent of 0.4:2.6:5.3:0.7. MWP-2′ was composed of Ara, Man, Gal and Glc in a molar percent of 0.5:1.4:2.1:0.4. In vitro study showed that both polysaccharides samples were able to stimulate the production of secretory molecules (NO, TNF-α and IL-6) of RAW264.7 murine macrophages in a dosage dependent manner. MWP-2′ seemed to be the most potent and induced significantly higher the NO production. These findings suggest that the ultrasonic treatment polysaccharides isolated in our study have immune potentiation effects on macrophages.